PERBAIKAN KUALITAS KADAR AIR DAN KADAR KOTORAN CRUDE PALM OIL (CPO) PADA MESIN PURIFIER MENGGUNAKAN KAIZEN DI PT. ACL - Nina Hairiyah; Ma'ratus Sholikhah (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
Moisture content and dirt content are important parameters to determine the quality of Crude Palm Oil (CPO) products produced by Palm Oil Mills. In recent periods, the quality of moisture content and dirt content at the clarification station for the purifier machine at PT. ACL does not meet the specified standards, namely for moisture content of more than 0.2% and impurities content of more than 0.5% for CPO samples coming out of the purifier machine. This research was conducted to improve the quality of the water content and dirt content of CPO on the purifier machine using kaizen at PT. ACL. The results of the kaizen analysis using the 5W+1H method were applied to take corrective actions. Based on observations, after corrective action was taken, the results obtained moisture content and dirt content that did not exceed the established standards so as to improve the quality of CPO produced by PT. ACL.